EFFICIENCY APPLICATIONS OF DOMESTIC PUMPKIN ROOTSTOCKS FOR GRAFTING CUCUMBER IN PROTECTED GROUND - Shoibekova A. Zh.,; Dzhantassov S.K.,; Nussupova A.O., (Academic Journal of Physical and Chemical Sciences, 2021)
When growing herbaceous vegetable crops in the world practice, great importance is given to the use of grafting method. The development of environmentally safe methods to increase the yield and resistance of plants to adverse growing conditions is very relevant in vegetable production. One such method in pumpkin crops is grafting. The aim of our work was to study the effect of domestic pumpkin rootstock on growth, development and yield characteristics of cucumber hybrid using grafting method. Grafting on pumpkin species improved the growth and development of plants depending on the rootstock, compared with rootstock plants. The aim of our research was to study the influence of domestic pumpkin rootstock on the growth, development and yield characteristics of the cucumber hybrid (scion). As a scion, the variety (Asylum), recommended for cultivation in protected ground conditions, was used, which was grafted on five domestic rootstocks: 1 (Mozoleevskaya 10), 2 (Karina), 3 (Aphrodite), 4 (Mindalnaya) and Russian selection 5 (Stofuntovaya) pumpkins from vegetable and melon crops. According to the generally accepted method, the graft was grafted (cucumber Asylum) on the rootstocks of pumpkin. Using a sample of pumpkin 1 (Mozoleevskaya 10), flowering began on the fifth day earlier in comparison with non-grafted plants, and when grafting on a sample of pumpkin 4 (Aphrodite), the fruit ripened earlier by six days. To get the greatest increase in early productivity by 30%, it is possible to use both rootstocks. A significant increase in total yield was provided by samples of rootstocks 2 (Karina) – 3.9 kg/m2 and 3 (Stofuntovaya) - 8.0 kg/m2 . The grafted cucumber plants with all the rootstocks used were superior to the root ones in height, in terms of the percentage of marketability of fruits and in terms of fruit weight. At the beginning of fruiting on grafted cucumber plants, the number of female flowers increased depending on the sample. In all grafted plants, the dry matter content in the fruit increased significantly. Because of our research, rootstocks 2 (Karina) and 3 (Stofuntovaya) were noted, which are recommended for use in further research breeding work and the production of grafted plants.